A Fragile Inheritance Radical Stakes in Contemporary Indian Art - Mathur, Saloni (Duke University Press, 2019)
In A Fragile Inheritance Saloni Mathur investigates the work of two seminal figures from the global South: the New Delhi-based critic and curator Geeta Kapur and contemporary multimedia artist Vivan Sundaram. Examining their written and visual works over the past fifty years, Mathur illuminates how her protagonists' political and aesthetic commitments intersect and foreground uncertainty, difficulty, conflict, and contradiction. This book presents new understandings of the culture and politics of decolonization and the role of non-Western aesthetic avant-gardes within the discourses of contemporary art. Through skillful interpretation of Sundaram's and Kapur's practices, Mathur demonstrates how received notions of mainstream art history may be investigated and subjected to creative redefinition. Her scholarly methodology offers an impassioned model of critical aesthetics and advances a radical understanding of art and politics in our time.